Effect of Soil Amendments, Variety and Irrigation Interval on Soil Properties and Yield of Sugarcane of a Salt-Affected Soil At Assalaya Sugar Scheme, Sudan - A. Mukhtar, Salaheldin; I. Adam, Adam; S.Ibrahim, Abu Elhassan (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
An experiment was conducted during February 1993 at Assalaya Sugar Scheme (Sudan), to study the effects of soil amendments, irrigation intervals and cane varieties on some physical and chemical properties of a salt-affected soil as well as yield of sugarcane. The experimental design was a split-split plot with three replications. Application of four tonnes/ha of a combination of filtermud and bagasse significantly increased soil moisture content compared to that of other amendments. Soil amendments decreased ESP and increased saturation percentage which in turn decreased ECe and SAR especially under 10 day irrigation interval. The highest cane yield       ( 158.8 t ha -1 ( was obtained by the addition of filtermud and bagasse. Variety C06806 with a mean cane yield of 146.6 t ha -l outyielded C0527 by about 27%, and the 10 day irrigation interval produced about 25% more cane than that of the 15 day irrigation interval. C06806 is suggested to be grown under the amendment of four tonnes/ha of filtermud and bagasse and irrigation interval of 10 days to give the highest cane yield in the salt-affected soil at Assalaya Sugar Scheme.